2008
DOI: 10.1371/journal.ppat.1000228
|View full text |Cite
|
Sign up to set email alerts
|

GEF-H1 Mediated Control of NOD1 Dependent NF-κB Activation by Shigella Effectors

Abstract: Shigella flexneri has evolved the ability to modify host cell function with intracellular active effectors to overcome the intestinal barrier. The detection of these microbial effectors and the initiation of innate immune responses are critical for rapid mucosal defense activation. The guanine nucleotide exchange factor H1 (GEF-H1) mediates RhoA activation required for cell invasion by the enteroinvasive pathogen Shigella flexneri. Surprisingly, GEF-H1 is requisite for NF-κB activation in response to Shigella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 57 publications
(68 reference statements)
4
100
0
Order By: Relevance
“…The mechanisms by which these NLRs regulate DC function have not been determined. There is also precedent in other cell types for GEF-dependent NLR activation during bacterial cell invasion, although it is unknown whether this occurs via direct protein interaction (19). Therefore, it was possible that lack of DC migration in the NLRP10-deficient mice could result from positive regulation of DOCK8 by NLRP10; however, our subsequent studies in fact suggested that DOCK8 functions independent of NLRP10.…”
Section: Resultsmentioning
confidence: 89%
“…The mechanisms by which these NLRs regulate DC function have not been determined. There is also precedent in other cell types for GEF-dependent NLR activation during bacterial cell invasion, although it is unknown whether this occurs via direct protein interaction (19). Therefore, it was possible that lack of DC migration in the NLRP10-deficient mice could result from positive regulation of DOCK8 by NLRP10; however, our subsequent studies in fact suggested that DOCK8 functions independent of NLRP10.…”
Section: Resultsmentioning
confidence: 89%
“…GEF-H1 is also activated by various pathogens, junction dissociation, and tissue disruption (28,30,40,41). Moreover, ZONAB is stimulated by reduced expression of ZO-1, a cellular inhibitor of the transcriptional and posttranscriptional function of ZONAB, linking it to the integrity of tight junctions (10).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the lack of amplified IL-8 production or MAPK activation following NOD1 and/or RICK over-expression may suggest the involvement of additional signaling molecules, which are required for initial host responses to H. pylori. Indeed, Fukazawa et al (70), recently found that the guanine nucleotide exchange factor was critical for the NOD1-dependent signaling responses to S. flexneri. It may be that molecules such as guanine nucleotide exchange factor are also required for the initiation of NOD1-mediated proinflammatory signal cascades during H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%